(untitled) (Revista científica Olimpia, 2025)
The research aims to develop the process of teaching swimming specify that the learning of a certain aquatic skill is developed by the union of different partial skills, in a single skill, that is, by the transformation of each of these particular skills into sub-objectives at the service of a greater skill, considering mandatory and prior the learning of aquatic motor skills in which they include flotation, propulsion, breathing, among others. Aquatic motor skills are also defined by some Cuban authors as basic motor qualities, a criterion that we will asume in this research for the optimal acquisition of aquatic sports skills (swimming, water polo). Various methods and techniques were used in the research: analytical-synthetic, inductive-deductive, observation, measurement, document analysis, and descriptive statistics. The application of the methods made it possible to know the insufficiencies that coaches have on the subject, the limitations of the Swimming Athlete Preparation Program, the results of the technical tests carried out on the athletes. Therefore, it is concluded that the technical preparation process of the athletes of the 5 to 7 years old category of the Municipal Sports School "Vicente Quesada Oconor" of Granma presents insufficiencies of the aquatic motor skills in its conception and realization due to various objective and subjective factors.